DMart an ace in India's retail space. Issue 1 (21st May 2021) - Mittal, Ankur; Jain, Anshul; Dhingra, Tarun
Abstract : Learning outcomes: The instructor can use this for covering the concept of competitive advantage and valuation. To explore the relationship between superior profitability with business model and identify the source of competitive advantage. Determining the value of business through discounted cash flow (DCF) approach. Case overview/synopsis: This case is based on the growth path of a retail chain company, DMart (Avenue Supermarket Private Limited), in the rapidly growing organized retail industry in India. It operates a unique business model that garners significant revenue growth with high profitability. The case covers the competitive advantages of DMart with respect to its peers and its valuation through the DCF model. Complexity academic level: The case is suitable for teaching basic courses in corporate valuation and strategy at the post-graduate level. The following courses can also make use of this case: financial management, corporate finance and strategic management in emerging markets. Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS 1: Accounting and Finance.